On some qualitative properties of monotone linear extensions of dynamical systems - Grechko, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We study monotone linear extensions of dynamical systems. The problem of existence of invariant manifolds and exponential separation is investigated for linear extensions on vector bundles that preserve the order structure. We also study the relationship between the monotonicity of linear extensions and the existence of bounded solutions of inhomogeneous linear extensions (weak regularity, quasiregularity).